Hydrazone derivatives in agrochemical discovery and development - Wang, Ya; Guo, Shengxin; Yu, Lijiao; Zhang, Wei; Wang, Zhenchao; Chi, Yonggui Robin; Wu, Jian (Chinese chemical letters, 2024)
As a common active substructure, hydrazone has attracted increasing attention and is considered essential for pesticide discovery. It has been widely regarded as a potential insecticidal, antibacterial, antifungal, antiviral, and herbicidal agent. In this review, we highlight the pesticide versatility of hydrazone fragments and provide a comprehensive summary of the biological activity, structure-activity relationship analysis (SARs), and primary mechanism of their analogs. This profile is expected to give valuable information for discovering new pesticides. As a common active substructure, hydrazone has attracted more and more attention and is considered an essential element for pesticide discovery. [Display omitted]